Surface aided polarization reversal in small ferroelectric particles - Chew, Khian Hooi; Chan, H.L.W.; Osman, J.; Stamps, R.L.; Tilley, D.R.; Shin, F.G. (2003)
Polarization reversal in ferroelectric particles driven by a pulsed electric field is examined theoretically using Landau-Devonshire-Khalatnikov theory. A significant reduction in reversal times is shown to be possible if certain surface properties and size criteria are met. The surface properties are also shown to control the magnitude of the applied field needed for irreversible switching. An interesting signature of surface effects is found in the switching current. The theory predicts that the switching current for small ferroelectric particles can exhibit double peaks as a function of time. The size and relative times of the peaks provide specific information on the magnitude and rate of surface reversal dynamics. (C) 2003 American Institute of Physics.